Smittia solominae sp. nov. (Diptera: Chironomidae: Orthocladiinae), living on ice of high mountain glaciers of the Elbrus Region (North Caucasus) - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2024)
Illustrated morphological description with a study of DNA barcoding and biology of adult male, pupa and larva of Smittia solominae sp. nov., living on the ice surface of glaciers at an altitude of about 3000 m above sea level in the Elbrus region of the North Caucasus is given. DNA barcoding provided support that the new species unique within genus Smittia. The average interspecific distances between S. solominae sp. nov. and other Smittia from BOLD above 12% that correspond to species level.